К.РАХМАНОВТЫҢ «АҚЫБЕТ» РОМАНЫНДА ФРАЗЕОЛОГИЗМЛЕРДИҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИКЛЕРИ - Досжанова, Г.Д. (FAN va JAMIYAT, 2017)
The article is devoted to the study of phraseologisms used in the novel “Akibet” by K.Rakhmanov. The author of the article analyses peculiarities of using pharaseological synonyms and variants.